2022
DOI: 10.3389/fgene.2022.862972
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of N6-Methyladenosine Regulators in the Subcluster Classification and Drug Candidates Prediction of Severe Obstructive Sleep Apnea

Abstract: Background: Obstructive sleep apnea (OSA) is the most common type of sleep apnea that impacts the development or progression of many other disorders. Abnormal expression of N6-methyladenosine (m6A) RNA modification regulators have been found relating to a variety of human diseases. However, it is not yet known if m6A regulators are involved in the occurrence and development of OSA. Herein, we aim to explore the impact of m6A modification in severe OSA.Methods: We detected the differentially expressed m6A regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Strausz et al conducted the first large‐scale GWAS of OSA using the FinnGen data set (217,955 patients) of 16,761 patients with OSA and demonstrated that a variant locus rs9937053 near the FTO gene was associated with OSA and linked with BMI [96]. Furthermore, patients with severe OSA showed dysregulated expression levels of m6A regulators, including HNRNPA2B1, KIAA1429, ALKBH5, YTHDF2, FMR1, IGF2BP1, and IGF2BP3 [97]. IH is a major feature of OSA that promotes lipolysis and the release of FFAs by significantly reducing the levels of m6A‐modified monoacylglycerol lipase (MGLL) mRNA through the downregulation of METTL3 [78].…”
Section: Association Between M6a Methylation and Osamentioning
confidence: 99%
“…Strausz et al conducted the first large‐scale GWAS of OSA using the FinnGen data set (217,955 patients) of 16,761 patients with OSA and demonstrated that a variant locus rs9937053 near the FTO gene was associated with OSA and linked with BMI [96]. Furthermore, patients with severe OSA showed dysregulated expression levels of m6A regulators, including HNRNPA2B1, KIAA1429, ALKBH5, YTHDF2, FMR1, IGF2BP1, and IGF2BP3 [97]. IH is a major feature of OSA that promotes lipolysis and the release of FFAs by significantly reducing the levels of m6A‐modified monoacylglycerol lipase (MGLL) mRNA through the downregulation of METTL3 [78].…”
Section: Association Between M6a Methylation and Osamentioning
confidence: 99%